2005
DOI: 10.1093/aje/kwi140
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Degeneration and Other Eye Disorders in Wives of Farmer Pesticide Applicators Enrolled in the Agricultural Health Study

Abstract: Retinal degeneration is the leading cause of visual impairment in older adults. An association between retinal degeneration and fungicide use was observed previously among farmer pesticide applicators in the Agricultural Health Study, a large study of farm families from Iowa and North Carolina. The objective of this investigation was to determine whether wives of these farmer pesticide applicators were at increased risk of retinal degeneration. Self-reported cross-sectional data obtained via questionnaire betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…Studies of physical injury (Sprince et al 2002(Sprince et al , 2003a(Sprince et al , 2003b(Sprince et al , 2003c(Sprince et al , 2007, mortality (Blair et al , 2005bLee et al 2007a), respiratory disorders (Hoppin et al 2002aValcin et al 2007), neurologic symptoms , retinal degeneration (Kamel et al 2000;Kirrane et al 2005), diabetes (Montgomery et al 2008;Saldana et al 2007), menstrual cycle characteristics (Farr et al 2004(Farr et al , 2006, hearing loss (Crawford et al 2008), Parkinson's disease (Kamel et al 2007b), changes in serum androgen levels (Martin et al 2002), arthritis (De Roos et al 2005b), depression (Beseler et al 2006(Beseler et al , 2008, and immune responses have also been conducted as part of the AHS but are not discussed in this review.…”
Section: A Review Of Pesticide Exposure and Cancer Incidence In The Amentioning
confidence: 99%
“…Studies of physical injury (Sprince et al 2002(Sprince et al , 2003a(Sprince et al , 2003b(Sprince et al , 2003c(Sprince et al , 2007, mortality (Blair et al , 2005bLee et al 2007a), respiratory disorders (Hoppin et al 2002aValcin et al 2007), neurologic symptoms , retinal degeneration (Kamel et al 2000;Kirrane et al 2005), diabetes (Montgomery et al 2008;Saldana et al 2007), menstrual cycle characteristics (Farr et al 2004(Farr et al , 2006, hearing loss (Crawford et al 2008), Parkinson's disease (Kamel et al 2007b), changes in serum androgen levels (Martin et al 2002), arthritis (De Roos et al 2005b), depression (Beseler et al 2006(Beseler et al , 2008, and immune responses have also been conducted as part of the AHS but are not discussed in this review.…”
Section: A Review Of Pesticide Exposure and Cancer Incidence In The Amentioning
confidence: 99%
“…Following adjustment for age and state of residence, there was a significant risk of retinal degeneration in women who had used fungicides (OR=1.9, 95% CI=1.2-3.1). In general, pesticide exposure appeared to be associated with retinal degeneration (23,24).…”
Section: Ocular Toxicitymentioning
confidence: 99%
“…The toxic effect of pesticides may be progressive, and over time may cause significant damage to the eyes. A major cause of visual impairment is retinal degeneration, whose occurrence is associated with several risk factors, such as age, hypertension, light exposure, smoking, alcohol, and obesity (23,24). It has been shown that pesticide exposure is also a likely risk factor for the occurrence of retinal degeneration.…”
Section: Ocular Toxicitymentioning
confidence: 99%
“…Parkinson's disease, a neurodegenerative disorder, is caused by some herbicides and fungicides (Costa et al 2008). One of the agricultural health study reported that wives and the applicator farmers of fungicides observed the risks of their retinal deterioration (Kamel et al 2000;Kirrane et al 2005;Hines et al 2008).…”
Section: Effects On Human Healthmentioning
confidence: 99%